An Evaluation of Bert B. Beach's Views on Ecumenism - Langhu, Koberson (Fakultas Filsafat Universitas Advent Indonesia, 2025)
Bert Beverly Beach (1928-2022) was the leading Adventist theologian and an authority on Christian ecumenism. His foremost contribution to Adventist theology is his magnum opus, Ecumenism: Boon or Bane? He presents a broad overview of both the historical backgrounds and the major current issues of concern regarding the modern ecumenical movement. Beach died in 2022 but his views are well and alive. They have been a point of controversy and debate among Adventist theologians. The main purpose of the study is to review whether Beach’s views on ecumenism are consistent with the development of Adventists’ attitude to ecumenism in its mission. It employs a literary research methodology based on available historical and theological data. The study reveals that Beach possesses a positive outlook on ecumenism, advocating for Adventists to engage in dialogue and collaboration with other Christian denominations. However, it fails in some major aspects, such as the potential dilution of Adventist distinctiveness. The Adventist Church continues its engagement in ecumenical activities while upholding its theological distinctiveness. Thus, Beach’s views while not accepted in their entirety are acknowledged and valued for shaping the Church’s approach to ecumenism.